Impact of Time-Varying Intensity of Mechanical Ventilation on 28-Day Mortality Depends on Fluid Balance in Patients With Acute Respiratory Distress Syndrome: A Retrospective Cohort Study - Hu, Weiwei; Zhang, Suming; He, Zhengyu; Zhou, Yang; Wang, Ziwen; Zhang, Yang; Zang, Baohe; Zhao, Wenjing; Chao, Yali (Frontiers in Medicine, 2022)
Background Recent studies have mainly focused on the association between baseline intensity of mechanical ventilation (driving pressure or mechanical power) and mortality in acute respiratory distress syndrome (ARDS). It is unclear whether the association between the time-varying intensity of mechanical ventilation and mortality is significant and varies according to the fluid balance trajectories. Methods We conducted a secondary analysis based on the NHLBI ARDS Network’s Fluid and Catheter Treatment Trial (FACTT). The primary outcome was 28-day mortality. The group-based trajectory modeling (GBTM) was employed to identify phenotypes based on fluid balance trajectories. Bayesian joint models were used to account for informative censoring due to death during follow-up. Results A total of 1,000 patients with ARDS were included in the analysis. Our study identified two phenotypes of ARDS, and compared patients with Early Negative Fluid Balance (Early NFB) and patients with Persistent-Positive Fluid Balance (Persistent-PFB) accompanied by higher tidal volume, higher static driving pressure, higher mechanical power, and lower PaO2/FiO2, over time during mechanical ventilation. The 28-day mortality was 14.8% in Early NFB and 49.6% in Persistent-PFB (p < 0.001). In the Bayesian joint models, the hazard ratio (HR) of 28-day death for time-varying static driving pressure [HR 1.03 (95% CI 1.01–1.05; p < 0.001)] and mechanical power [HR 1.01 (95% CI 1.002–1.02; p = 0.01)] was significant in patients with Early NFB, but not in patients with Persistent-PFB. Conclusion Time-varying intensity of mechanical ventilation was associated with a 28-day mortality of ARDS in a patient with Early NFB but not in patients with Persistent-PFB.